CORRELATION BETWEEN CADMIUM CONCENTRATION AND TOTAL ORGANIC MATTER IN SEDIMENTS AT TALLO ESTUARY, MAKASSAR CITY, INDONESIA - Tiri, Liana Nayna Putri Rustam; Samawi, Muhammad Farid; Jalil, Abd Rasyid; Werorilangi, Shinta; Umar, Widyastuti (Hasanuddin University, 2023)
This study aims to determine the distribution and relationship between the concentration of cadmium metal (Cd) and total organic matter (TOM) in sediments in the Tallo estuary, Makassar City. The study collected sediment samples from 12 points, distance of 500m between points sampling. Furthermore, 12 sediment samples were analyzed for Cd and TOM concentrations in the laboratory. The results of measurements of Cd metal in sediments showed concentrations ranging from 0.001 - 0.037 mg/kg. The concentration of Cd metal found was still in the low category. While the concentration of TOM in sediment ranges from 6.7 -30.3%, indicating a low concentration. The distribution of Cd and TOM showed that the farther from the estuary, the lower the concentration. Based on the results of the regression test, the relationship between Cd and TOM concentrations was 80.1%. This shows that the accumulation of Cd metal in Tallo River sediments is strongly influenced by the concentration of organic matter.